Conspicuous Daughters: Exogamy, Marriage Expenditures, and Son Preference in India. - Robitaille, Marie-Claire (Journal of Development Studies, 2020)
The literature on son preference postulates a strong link between marriage expenditures, dowry practices, and son preference, leading to the elimination of female foetuses and important discriminatory practices against girls. This statement, however, has not, as far as I know, been tested empirically using a representative sample of the Indian population. Using data from the India Human Development Survey (IHDS) conducted in 2005, this paper shows that marriage expenditures by the bride's family and dowry payments reduce stated son preference, ceteris paribus, supporting the idea that the bride's family's marriage expenditures and dowries are Veblen goods. The results, therefore, support the sankritisation theory, as expensive marriage practices are used to enhance social status. This result is robust to a series of robustness check, including the use of revealed son preference. The main drivers behind son preference appear to be exogamy and the need for old age support. Other important factors are religious beliefs and access to modern information (education and media). Finally, this article also shows that lavish marriage expenditures, for both groom's and bride's family, reduce fertility.